E-Learning as computer games: Designing immersive and experiential learning - Siang, , AC; Rao, , GSVRK (2004)
The article presents the academic views of narrative in the interactive environment particularly in computer games. The relationship between stories and games is examined from the perspective of ludology and narratology in order to understand how computer games work as a medium for storytelling. E-Learning software is thus analyzed as computer games and several issues pertaining to the lethargic stage of educational software development are raised. Then, two versions of e-Learning prototypes are demonstrated and discussed.